An illustrated account of Stethorini (Coleoptera: Coccinellidae) predatory on mite pests of banana in India, including description of a new species - Poorani, J.; Anuradha, C.; Thanigairaj, R. (Zootaxa, 2025)
Mite pests cause moderate to severe foliar damage in bananas and plantains during summer in India. Though the extent of mite damage on banana during dry spells is often severe, it goes undetected because the symptoms of mite damage are similar to those caused by nutritional deficiency and moisture deficit stress. Many species of Stethorini (Coleoptera: Coccinellidae), staphylinid beetles and predatory thrips keep the pest mite populations on bananas in check. In this paper, illustrated diagnostic accounts of seven species of Stethorini, including one species of Parastethorus Pang & Mao and six species of Stethorus Weise, that are commonly associated with banana mites in southern states of India are given, with details of distribution, and immature stages, wherever available. One new species, Stethorus (Allostethorus) indicus sp. nov., commonly collected as a predator of spider mites on banana and coconut, is described from Southern India.